Responses of photosynthesis to high temperatures in oak saplings assessed by chlorophyll-a fluorescence: inter-specific diversity and temperature-induced plasticity - Daas, C.; Montpied, P.; Hanchi, B.; Dreyer, E. (Annals of forest science, 2008)
• The sensitivity of photosynthesis to high temperature was investigated in greenhouse-grown saplings of three Mediterranean (Quercus canariensis Willd., Q. coccifera L. and Q. suber L.) and two temperate European oak species (Q. robur L. and Q. petraea Matt. Liebl.). The sensitivity to high temperature was inferred from F0T curves producing the critical temperature (Tc ) at which a rapid rise in ground chlorophyll a ﬂuorescence (F0) occurs. Tc is known to acclimate to moderately increased ambient temperature by displaying signiﬁcant increases. • We ﬁrst checked whether acclimation of Tc was paralleled by an increase in optimal temperature for light driven electron ﬂux (Topt ,), recorded by measuring quantum yield of photochemistry under saturating CO2 and moderate irradiance. Saplings of Q. suber and Q. canariensis were submitted to four, ﬁve days long ambient temperature steps (15, 25, 35 and 15 ◦ C again). Tc was usually largely above 45 ◦ C while Topt was around 30–35 ◦ C. Both increased with ambient temperature in the two species, and decreased again when temperature returned to the initial values. This recovery was nevertheless not complete after a week at 15 ◦ C. • A second experiment tested whether the plasticity of Tc was of the same extent in the ﬁve species. A signiﬁcant increase of Tc followed by a decrease was detected in all species. Only small inter-speciﬁc diﬀerences were detected in Tc , and temperature induced plasticity was similar in the diﬀerent species: Tc increased by about 4–5 ◦ C while ambient temperature was increased from 15 to 35 ◦ C. Mediterranean and European oaks did not diﬀer in this respect. • This result does not support the hypothesis that oak species from warmer regions would display a larger plasticity of Tc in response to increasing temperatures.
Keywords: optimal temperature; Photochemistry; quantum yield; Quercus canariensis; Quercus coccifera; Quercus petraea; Quercus robur; Quercus suber

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.81710.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Maturation and germination of oak somatic embryos originated from leaf and stem explants: RAPD markers for genetic analysis of regenerants. - Sánchez, M. Concepción; Martínez, M. Teresa; Valladares, Silvia; Ferro, Enrique; Viéitez, Ana M. (Journal of plant physiology, 2003)
Experiments were performed to determine the influence of maturation medium carbohydrate content on the rates of germination and plantlet conversion (root and shoot growth) of somatic embryos from four embryogenic lines derived from leaf or internode explants of Quercus robur L. seedlings. The conversion rate was favoured by high carbohydrate content as long as the maturation medium contained at least 2% sucrose, which was necessary for healthy embryo development. Given this, sorbitol and mannitol favoured the conversion rate more efficiently than sucrose, the highest rate, 32%, being achieved by medium with 6% sorbitol and 3% sucrose. Maturation treatment did not affect the root or shoot lengths of converted embryos. In supplementary experiments, 2 weeks of gibberellic acid treatment between maturation and germination treatments did not improve germination rates, but did reduce root length and the number of leaves per regenerated plantlet. In the four embryogenic lines tested, plant recovery rate was enhanced by inclusion of benzyladenine into the germination medium following culture of the embryos on maturation medium with 6% sorbitol and 2-3% sucrose. In embryogenic systems it is important to assess the uniformity of the regenerants. Random amplified polymorphic DNA (RAPD) analysis using 32 arbitrary oligonucleotide primers was performed to study variability in DNA sequences within and between four embryogenic lines. No intraclonal nor interclonal polymorphism was detected between embryogenic lines originating from different types of explant from the same seedling, but every one of the primers detected enough polymorphism among clones originating from different plants to allow these three origins to be distinguished. No differences in DNA sequences between regenerated plantlets and their somatic embryos of origin were detected, but a nodular callus line that had lost its embryogenic capacity was found to be mutant with respect to three other clones originating from the same plantlet. This study shows that high carbohydrate levels in the maturation medium significantly increase plant conversion of oak somatic embryos, which exhibit no variation in DNA sequences when proliferated by secondary embryogenesis.
The following values have no corresponding Zotero field: accession-num: 12872492
Keywords: DNA polymorphism; genetic stability; plant conversion; Quercus robur; Somatic embryogenesis